Urine high–sensitive troponin I in children cannot offer an applicable alternative to serum - Bakoš, Matija; Dilber, Daniel; Jazbec, Anamarija; Svaguša, Tomo; Potkonjak, Ana-Meyra; Braovac, Duje; Đurić, Željko; Radeljak, Andrea; Lončar Vrančić, Ana; Vraneš, Hrvoje; Galić, Slobodan; Novak, Milivoj; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction In children, congenital heart defects represent the primary cause of increased serum troponin I. The elimination process of cardiac troponin I from the bloodstream and the factors influencing this process remain unknown. The objective of this study was to explore the role of troponin I as an indicator of cardiac damage in children both in serum and urine, a concept previously investigated in adults. Methods Our prospective study involved 70 children under 24 months of age. The first group underwent ventricular septal defect repair, while the second group involved children who had undergone partial cavopulmonary anastomosis. For these groups, urine and serum troponin I were assessed on four occasions. The third group, consisting of healthy children, underwent a single measurement of urine troponin I. Results Serum troponin I values exhibited an expected elevation in the early postoperative period, followed by a return to lower levels. Significantly higher concentrations of serum troponin I were observed in the first group of children (p < 0.05). A positive correlation was found between troponin I in the first three measurements and cardiopulmonary bypass and aortic cross-clamping time. There was no discernible increase in urine troponin I directly related to myocardial damage; troponin I couldn't be detected in most urine samples. Discussion The inability to detect troponin I in urine remains unexplained. Potential explanatory factors may include the isoelectric point of troponin I, elevated urinary concentrations of salts and urea, variations in urine acidity (different pH levels), and a relatively low protein concentration in urine.